Employment of targeted nanoparticles for imaging of cellular processes in cardiovascular disease. (December 2020) - Modak, Mallika; Frey, Molly A; Yi, Sijia; Liu, Yugang; Scott, Evan A
Abstract : Cardiovascular disease (CVD) is a leading cause of global mortality, accounting for pathologies that are primarily of atherosclerotic origin and driven by specific cell populations. A need exists for effective, non-invasive methods to assess the risk of potentially fatal major adverse cardiovascular events (MACE) before occurrence and to monitor post-interventional outcomes such as tissue regeneration. Molecular imaging has widespread applications in CVD diagnostic assessment, through modalities including magnetic resonance imaging (MRI), positron emission tomography (PET), and acoustic imaging methods. However, current gold-standard small molecule contrast agents are not cell-specific, relying on non-specific uptake to facilitate imaging of biologic processes. Nanomaterials can be engineered for targeted delivery to specific cell populations, and several nanomaterial systems have been developed for pre-clinical molecular imaging. Here, we review recent advances in nanoparticle-mediated approaches for imaging of cellular processes in cardiovascular disease, focusing on efforts to detect inflammation, assess lipid accumulation, and monitor tissue regeneration.